Experimental analysis of process parameter effects on vibrations in the high-speed grinding of a camshaft - Liu, Tao (Strojniški vestnik, 2020)
The capacity to minimize vibrations in grinding by the selection of appropriate process parameters is a significant benefit in the process optimization of cam grinding. This paper presents survey methods to characterize and quantify the vibrations and waviness in a camshaft grinding application. First, a modal analysis was conducted to study the dynamic characteristic of a camshaft grinding machine. Then, developed methods were applied to study the influences of various parameters on vibrations in the high-speed grinding of a camshaft. Furthermore, the influence of each grinding process condition on surface waviness in high-speed camshaft grinding was studied. The results show that the vibrations and the surface waviness change with the increase of grinding depth, and an appropriate grinding wheel speed combined with a workpiece speed has, for most grinding conditions, a reducing effect on vibration magnitudes and waviness. Finally, the specific indications about the optimal grinding process parameters in terms of dynamic characteristics of the grinding machine were given, and the speed ratio=1.2 is a novel choice.
Keywords: camshafts; drdranje; frekvenčni spekter; frequency spectrum; high-speed grinding; modalna analiza; odmične gredi; surface waviness; valovitost površine; vibracije; vibrations; visokohitrostno brušenje